Computer, network, software, and hardware engineering with applications - Schneidewind, Norman (Piscataway, NJ : IEEE Press ; Hoboken, N.J. : John Wiley & Sons, 2012)
There are many books on computers, networks, and software engineering but none that integrate the three with applications. Integration is important because, increasingly, software dominates the performance, reliability, maintainability, and availability of complex computer and systems. Books on software engineering typically portray software as if it exists in a vacuum with no relationship to the wider system. This is wrong because a system is more than software. It is comprised of people, organizations, processes, hardware, and software. All of these components must be considered in an integrative fashion when designing systems. On the other hand, books on computers and networks do not demonstrate a deep understanding of the intricacies of developing software. In this book you will learn, for example, how to quantitatively analyze the performance, reliability, maintainability, and availability of computers, networks, and software in relation to the total system. Furthermore, you will learn how to evaluate and mitigate the risk of deploying integrated systems. You will learn how to apply many models dealing with the optimization of systems. Numerous quantitative examples are provided to help you understand and interpret model results. This book can be used as a first year graduate course in computer, network, and software engineering; as an on-the-job reference for computer, network, and software engineers; and as a reference for these disciplines.
Part 1. Computer Engineering -- Digital Logic and Microprocessor Design -- Case Study in Computer Design -- Analog and Digital Computer Interactions -- Part 2. Network Engineering -- Integrated Software and Real-Time System Design with Applications -- Network Systems -- Future Internet Performance Models -- Network Standards -- Network Reliability and Availability Metrics -- Part 3. Software Engineering -- Programming LanguagesOperating Systems -- Software Reliability and Safety -- Part 4. Integration of Disciplines -- Integration of Hardware and Software Reliability -- Part 5. Applications -- Applying Neural Networks to Software Reliability Assessment -- Web Site Design -- Mobile Device Engineering -- Signal-Driven Software Model for Mobile Devices -- Object-Oriented Analysis and Design Applied to Mathematical Software -- Tutorial on Hardware and Software Reliability, Maintainability, and Availability Practice Problems with Solutions 1 -- Practice Problems with Solutions 2 -- Index.
Includes bibliographical references and index.
Print version record and online resource.
Keywords: Computer engineering; Computer networks; Software engineering; Electrical engineering; Engineering; Computer science; COMPUTERS -- Data Transmission Systems -- General; COMPUTERS -- Networking -- Vendor Specific; COMPUTERS -- Programming -- Open Source; COMPUTERS -- Software Development & Engineering -- General; COMPUTERS -- Software Development & Engineering -- Tools; Computer engineering; Computer networks; Software engineering; Electronic books